KONSEP MANAJEMEN STRATEGIK SEBAGAI PARADIGMA BARU DI LINGKUNGAN ORGANISASI PENDIDIKAN - Sujadi, Sujadi (JURNAL STIE SEMARANG, 2011)
From the above description the author can draw conclusions about the advantages and benefits of the implementation of strategic management in educational organizations, namely: Implementation of Strategic Management Excellence By applying strategic management, the educational organization (school) will have advantages,   such   as:   profitability,   produktifitasi   high,   has   a   competitive   position, technological superiority, the superiority of Human Resources, a conducive working climate, ethics and social responsibility is growing. Benefits of Strategic Management Benefits gained from the implementation of strategic management are: - A dynamic organization, - Control functions are operating effectively and efficiently - Negate difference and disagreement in realizing the benefits - Facilitate the agreed changes or the development of strategies to be implemented - Encourage proactive behavior for all parties to participate in realizing the advantages -Enhance   the   feeling   of   belonging,   active   participation   and   responsibility   for   all organizational components.